Utilization of Himawari-9 and Radiosonde Weather Satellite Data in Heavy Rainfall Analysis(Case Study: Semarang, 14 March 2024) - M. Alvin Faiz (Journal of Computation Physics and Earth Science (JoCPES), 2023)
The heavy rainfall event that hit Semarang City on 14 March 2024 caused flooding at several points. To understand the cause of this event, a comprehensive meteorological analysis is required. This research utilises Himawari-9 weather satellite data with RGB, day convective storm and 24-hour microphysics methods, as well as upper air observations using radiosonde at 12 UTC in the Semarang area. The use of this method is effective in knowing the atmospheric conditions in the Semarang area. The results of observations with the RGB method show cloud conditions that cause heavy rain with high intensity. Observations with the day convective storm method detect convective clouds that have the potential to cause heavy rain. The 24-hour microphysics method identifies High Cumulonimbus, Dense Cirrus, and Thick Cirrus cloud types that can cause heavy rain. Upper air observations with radiosonde at 12 UTC showed the early phase of severe weather in the Semarang area. The results of this study confirm the importance of satellite and radiosonde data integration in predicting and analysing heavy rain events for hydrometeorological disaster risk mitigation.